PENGARUH GOOD CORPORATE GOVERNANCE, KARAKTERISTIK PERUSAHAAN DAN UKURAN KAP TERHADAP FEE AUDIT EKSTERNAL - Marcella Octavia Chandra (Jurnal Akuntansi Bisnis, 2015)
This study aims to analyze factors that influence the determination of external audit fees on all companies listed on Bursa Efek Indonesia (BEI). The factors tested in this study are independency of the board commissioner, size of the board commissioner, the meeting intensity of the board commissioner, the meeting intensity of the audit committee, firm size, subsidiaries, auditor size, and client risk. Collecting data is using purposive sampling method to all company listed in Bursa Efek Indonesia (BEI) during 2009-2013. A total of 222 companies used as sample in this research. The result of this research showed that the meeting intensity of the board commissioner, firm size, subsidiaries, and auditor size have significant relationship on the external audit fees. However, independency of the board commissioner, size of the board commissioner, the meeting intensity of the audit committee, and client risk did not have significant influence with external audit fees.